Mineralogy, chemical properties and classification of soils from the eastern coast mountains in Santa Catarina State, Brazil (Revista de Ciências Agroveterinárias, 2009)
Information about genesis and mineralogical composition of Santa Catarina soils are scarce. The objectives of this work were to characterize the morphology, chemical, physical and mineralogical attributes of representative soil profiles of the eastern coast mountains of this region, to identify soil mineralogical composition and its relation with soil physical and chemical properties. Seven profiles of Ultisols and Oxisols (Argisols and Latosols in the Brazilian Classification System, respectively), derived from different lithologies, were selected for this study. Morphology of soils and physical aspects of the environment were described. Physical and chemical routine analyses were performed in the fine earth. In the clay fraction, samples were saturated with K, Mg and Mg plus ethylene glycol and analyzed by X-ray diffractometry. Silt was analyzed in powder. All soil profiles were acid, with low organic carbon and low sum of basis and basis saturation, indicating lixiviated and highly weathered soils. Clay soil composition was very similar among the soils. Kaolinite was the dominant clay mineral, with minor proportions of illite, vermiculite with hidroxy-Al interlayers and interstratified illite-vermiculite. Aluminum oxide (gibbsite) and quartz, were also detected in some profiles. Despite the occurrence of 2:1 clay minerals in some soils, CEC of clay was low, probably because these clay minerals have high hidroxy-Al interlayers, which reduce soil CEC.
Keywords: argisols; minerals; genesis; chemical properties.